2020
DOI: 10.35465/28.1.2020.pp20-30
|View full text |Cite
|
Sign up to set email alerts
|

Acpa in Saliva and Their Association With Periodontitis and Rheumatoid Arthritis

Abstract: Anti-cyclic citrullinated peptide antibodies (ACPA) are formed by the action of host-generated antigens and are part of the etiology of rheumatoid arthritis (RA). They are a sensitive and highly specific indicator of RA. MATERIALS AND METHODS In the study involved 105 subjects aged 32 to 85 years (Mean age 50,6 ±13,07), divided into four groups: Group I – with periodontitis (P) and without RA, with diagnosed osteoarthritis – 26 patients; Group II – with P and RA – 28 patients; Group III – without P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 6 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…On the other hand, data on the presence of citrullinated proteins and antibodies against them in periodontal tissues are known, as well as a positive relationship between the severity of periodontal inflammation and their concentration [25,26]. Confirmation of these facts is another study of ours, in which we found a significant positive correlation between the salivary ACPA levels and the severity of some periodontal indicators (PD and BoP) in patients with P, as well as a significant positive relationship between the ACPA concentration in saliva and RA-indicators ACPA in serum, RF in serum and DAS 28 (CRP) in patients with concomitant P and RA [27]. It is likely that the local production of ACPA in inflamed periodontal tissues could lead to a change in immune tolerance to citrullinated peptides and in predisposed individuals and existing rheumatoid disease to aggravate its course by stimulating systemic production of ACPA.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, data on the presence of citrullinated proteins and antibodies against them in periodontal tissues are known, as well as a positive relationship between the severity of periodontal inflammation and their concentration [25,26]. Confirmation of these facts is another study of ours, in which we found a significant positive correlation between the salivary ACPA levels and the severity of some periodontal indicators (PD and BoP) in patients with P, as well as a significant positive relationship between the ACPA concentration in saliva and RA-indicators ACPA in serum, RF in serum and DAS 28 (CRP) in patients with concomitant P and RA [27]. It is likely that the local production of ACPA in inflamed periodontal tissues could lead to a change in immune tolerance to citrullinated peptides and in predisposed individuals and existing rheumatoid disease to aggravate its course by stimulating systemic production of ACPA.…”
Section: Discussionsupporting
confidence: 87%
“…Two studies reported on the level of ACPA in saliva of RA patients with PD in comparison to RA patients without PD 34,57 . Both studies found the ACPA level was slightly lower in RA with PD than in RA without PD (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 795 reports which were regarded as irrelevant were excluded following screening of titles and abstracts. After retrieval and assessment of 136 eligible full‐text reports according to the selection criteria, 29 studies 12,13,33–59 were included in the qualitative analysis whereby for the quantitative analysis, data from 28 studies were used (Figure 1). The reasons for the exclusion of 107 articles following full‐text assessment were classified into four domains: (i) use of unclear or self‐reported measures to ascertain RA or PD, (ii) unclear or lack of comparison between RA with and without PD, (iii) absence of reporting on the levels of autoantibodies; and (iv) unpublished data or case reports (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to SpA, the pathogenesis of inflammation in rheumatoid arthritis (RA) is mediated by a number of effector cytokines (IL-6, IL-7, IL-10, IL-12, IL-15, IL-21, IL-23, IFNα and IFNβ) that signal using JAK [25,26,27]. The efficacy of treatment with Jak inhibitors has been demonstrated in multiple clinical trials in RA [28,29,30,31,32].…”
Section: Jak Inhibitorsmentioning
confidence: 99%